PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS BLOGGER DAN KECERDASAN LINGUISTIK TERHADAP HASIL BELAJAR BAHASA INDONESIA - Maftuhatul Fahmiyah; Khasanah Khasanah (Akademika, 2018)
This research was conducted at Islamic University '45 Bekasi for students majoring in Communication Science semester II of the 2017/2018 academic year with the aim of knowing the effect of blogger-based learning media and student linguistic intelligence on Indonesian learning outcomes. This study used a quantitative experimental method using the True Experimental Design Factorial 2x2. The data analysis technique used is two-way analysis of variance (two-way ANOVA). The affordable population in this study were students of the second semester majoring in Communication Science in 2017/2018. Sampling using saturated samples with simple random sampling technique. A sample of 100 students consisting of 50 students in the control group. Based on the results of the research with two-way Anava, the following results were obtained: 1) The results of learning Indonesian for students using blogger-based learning media were higher than those using power point-based learning media, as evidenced by obtaining Fcount = 27.673> Ftable = 3.072 2) Students 'Indonesian learning outcomes are influenced by the interaction between blogger-based learning media and students' linguistic intelligence, as evidenced by the price of Fcount = 4.265> Ftable = 3.072.3) Indonesian learning outcomes for students who have high linguistic intelligence who use blogger-based learning media superior to those using power point-based learning media as evidenced by the price q0 = 38.429> qt 1.65.4). The results of learning Indonesian for students who have low learning interest who use blogger-based learning media are superior to those using power point-based learning media as evidenced by the price of q0 2013> qt = 1.65. From the findings above, it can be concluded that the learning media of student bloggers affect the learning outcomes of the second semester students of the Department of Communication Studies at the Islamic University 45